2010
DOI: 10.1101/gad.1983810
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the PRC2 component Ezh2 is cell cycle-regulated and up-regulates its binding to ncRNA

Abstract: Ezh2 functions as a histone H3 Lys 27 (H3K27) methyltransferase when comprising the Polycomb-Repressive Complex 2 (PRC2). Trimethylation of H3K27 (H3K27me3) correlates with transcriptionally repressed chromatin. The means by which PRC2 targets specific chromatin regions is currently unclear, but noncoding RNAs (ncRNAs) have been shown to interact with PRC2 and may facilitate its recruitment to some target genes. Here we show that Ezh2 interacts with HOTAIR and Xist. Ezh2 is phosphorylated by cyclin-dependent k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
381
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(416 citation statements)
references
References 22 publications
(36 reference statements)
20
381
2
Order By: Relevance
“…Surprisingly, the interaction with nascent transcripts does not result in local H3K27 methylation nor in Polycomb mediated gene silencing, suggesting that a nascent transcript may be acting as an inhibitor/evictor for PRC2 or as a decoy for 'functional' RNA-protein interaction. Similar to HP1, interaction between Ezh2 and RNAs seems to involve a domain containing a short stretch of basic amino acids [53]. While HP1 has longer and denser patches of K/Rs, short stretches of K/Rs are present in most nuclear proteins as part of nuclear localization signals.…”
Section: Rna and Histone Modification Binding Can Influence Each Othermentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the interaction with nascent transcripts does not result in local H3K27 methylation nor in Polycomb mediated gene silencing, suggesting that a nascent transcript may be acting as an inhibitor/evictor for PRC2 or as a decoy for 'functional' RNA-protein interaction. Similar to HP1, interaction between Ezh2 and RNAs seems to involve a domain containing a short stretch of basic amino acids [53]. While HP1 has longer and denser patches of K/Rs, short stretches of K/Rs are present in most nuclear proteins as part of nuclear localization signals.…”
Section: Rna and Histone Modification Binding Can Influence Each Othermentioning
confidence: 99%
“…As discussed above, sumoylation of lysine residues in the hinge region of mouse HP1α controls its binding to major satellite transcripts [34]. Besides, phosphorylation of Ezh2 is known to enhance its binding to HOTAIR lncRNA [53]. Secondly, the histone modification binding proteins may use different interaction modes or surfaces for the promiscuous vs. specific RNA interaction.…”
Section: Rna and Histone Modification Binding Can Influence Each Othermentioning
confidence: 99%
“…The importance of PcG proteins in X-inactivation is suggested by the fact that the inactive X chromosome is enriched with H3K27me3 and H2AK119u1, which are posttranslational modifications mediated by Polycomb repressive complex (PRC) 2 and 1, respectively [48][49][50][51]. The recruitment of PRC2 complex in X-inactivation has been attributed to direct biochemical interaction of the catalytic subunit of the complex, Ezh2, with the A-repeats of Xist RNA [52] Mapping of the candidate RNA interaction domain of Ezh2 suggested that RNA binding requires site specific phosphorylation of Ezh2 [53]. Further to this, others have described an interaction between a different subunit of PRC2, Suz12, and Xist A-repeats [54].…”
Section: Rstbroyalsocietypublishingorg Phil Trans R Soc B 368: 2011mentioning
confidence: 99%
“…28 Further, CDK1-mediated phosphorylation of Thr345 on mouse Ezh2 (human Thr350) controls interaction with HOTAIR and Xist non coding (nc) RNAs and recruitment to specific target genes. 29 Target amino acid residues of Ezh2 can therefore be envisaged as chromatin sensors for different extra-cellular conditions, acting by modulating several properties of the protein such as chromatin binding, interaction with other PRC components or transcription factors and enzymatic activity.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%